1988
DOI: 10.1139/o88-057
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and mammalian thioredoxin systems activate iodothyronine 5′-deiodination

Abstract: The identity of a dithiol (designated DFB) of relative mass (Mr) = 13,000, reported previously to be present in fraction B of rat liver cytosol and to participate as a cofactor in the 5'-deiodination of iodothyronines, has been investigated. Substitution of highly purified thioredoxin from Escherichia coli for fraction B or of highly purified thioredoxin reductase from either E. coli or rat liver for cytosolic fraction A (containing DFB reductase) permits deiodination of 3,3',5'-[125I]triiodothyronine by rat l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Substitution experiments [25] showed that Escherichia coli thioredoxin could replace Fraction B. Highly purified thioredoxin reductase and thioredoxin of rat liver cytosol, together with NADPH, were shown by others to support 5'-deiodination of rT3 [25]. These various findings strongly suggested that the stimulatory activity that we reported in rat liver [7-9] could be attributed to the thioredoxin system.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Substitution experiments [25] showed that Escherichia coli thioredoxin could replace Fraction B. Highly purified thioredoxin reductase and thioredoxin of rat liver cytosol, together with NADPH, were shown by others to support 5'-deiodination of rT3 [25]. These various findings strongly suggested that the stimulatory activity that we reported in rat liver [7-9] could be attributed to the thioredoxin system.…”
Section: Discussionmentioning
confidence: 51%
“…Our previously reported investigations of the 5'-DI cofactor system of rat liver cytosol utilized partially purified chromatographic Fractions A and B, together with NADPH [7][8][9]25], and indicated that this system resembled the thioredoxin system in the following respects: (a) NADPH-dependence, (b) requirement for a reductase of Mr > 60000 plus a dithiol of Mr approx. 13000 and pl < 6, (c) sensitivity to arsenite and iodoacetamide, (d) resistance to thermal inactivation, (e) enhancement by DTT and (f) inhibition of 5'-DIsupportive activity of Fractions A and B by anti-(thioredoxin reductase) IgG and by anti-thioredoxin IgG respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A quite analogous system as proposed now for glycine reductase might also exist for the iodothyronine 5' deiodination. The required dithiol can be replaced by the thioredoxin system (7). The respective deiodinase has recently been identified as a selenoenzyme (3).…”
Section: Discussionmentioning
confidence: 99%
“…Thioredoxins were the first antioxidants identified in cells, and are known to act as general protein disulfide reductase enzymes [50] [52] . Thioredoxins are generally maintained in a reduced state in cells by accepting protons from NADPH via the enzyme thioredoxin reductase (TrxR) [35] , [36] , [52] . In order to determine whether CLIC protein enzymatic activity is linked to the TrxR system, CLIC1, CLIC2 and CLIC4 were assayed in a system containing TrxR, in place of GR.…”
Section: Resultsmentioning
confidence: 99%